Kajian Persentase Ruang Terbuka Hijau pada Implementasi Revitalisasi Taman Kota Malang - Juwito, Juwito; Wikantiyoso, Respati; Tutuko, Pindo (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
The â€œPark Revitalizationâ€ program initiated by the Malang City Government with the privatesector is being implemented and the implementation of this program raises questions, namely theextent to which this physical intervention should be carried out, so that integration andsustainability have a positive impact, without reducing the existing green open space. This studyuses a quantitative methodology in the form of a Green Open Revitalization program reviewconducted in Malang City by assessing the percentage reduction in area. Operational definitionsof variables used in this research design are in the form of transfer functions or building additionsand the use of functional areas / materials or cover material. Analysis of the condition of objects byreferring to Area Revitalization. Objects of observation are analyzed using thematic maps andstatistical analysis. The results of the study show that there is a close correlation between theconversion of functions or the addition of buildings and the use of functional areas/material orcover material to the percentage of RTH. The selection of the right material with the theme andcharacteristics of green open space with sustainable technology is an integrated entity with continuous improvement in the quality and quantity of the environment.Â DOI: https://doi.org/10.26905/lw.v11i1.2686